Stališča (bodočih) pedagoških delavcev kot temelj kakovostnega vključevanja otrok priseljencev - Lesar, Irena (Dve domovini, 2020)
Contemporary documents and guidelines, at both the national and EU levels, emphasize the importance of implementing the concept of inclusiveness, which also involves the principle of interculturalism. This paper provides insights into the attitudes of present and future teaching staff and towards intercultural education. The sample included 763 professional teachers and 411 students. Students expressed less negative attitudes toward immigrant children and more positive attitudes toward cultural diversity and helping immigrant children. The reasons for the negative attitudes and possible ways of promoting a change in the attitudes of the professional educational staff are discussed.
Keywords: attitudes; children migranst; inclusiveness; inkluzivnost; intercultural education; medkulturno izobraževanje; migracije; migration; otroci priseljenci; schools; stališča; šole; študenti; teacher trainees; teachers; učitelji